Beneficios de la lactancia materna en las madres que acuden al S.C.S 29 de Noviembre, Cantón Santa Rosa en el período, octubre diciembre del año 2013 - Tenesaca Ortiz, Katty E. (2014)
This research has as main objective to determine the knowledge possessed by women who bring their babies to the pediatric control in the health Sub-Centre quarter November 29, taking into account maternal age, education, marital status and occupation of mothers between other variables, for which I use as a research tool survey, this study is explanatory quantitative allowing us to describe to knowledge about breastfeeding with mothers, the objectives are aimed to promote and support breastfeeding.